The relationship between mandatory exercise and exercise habits in Chinese colleges and universities: an analysis of multiple mediating effects - Guo, Xiangxuan; Cao, Dawei; Wu, Dong; Kuang, Lulu (Frontiers in Psychology, 2025)
This study aims to explore the relationship between mandatory exercise and exercise habits in colleges and universities and to investigate the multiple mediating effects of self-efficacy and exercise attitudes. The study adopted convenience sampling, with 589 junior students as the research subjects, and conducted a questionnaire survey using professional scales. The results show that mandatory exercise in colleges and universities has a significant positive effect on the formation of exercise habits. Self-efficacy and exercise attitudes play a significant mediating role and chain mediating effect between mandatory exercise and exercise habits, with the direct effect being the most significant, followed by the chaining effect, the mediating effect of self-efficacy, and the mediating effect of exercise attitudes. This study further reveals the internal mechanism underlying the relationship between mandatory exercise and exercise habits, which is highly important for promoting the development of “exercise habits,” i.e., the overall development of college and university students.